Fast food preferences and food habits among students of private universities in Bangladesh (South East Asia Journal of Public Health, 2014)
Consumption of takeaway and fast food by young adolescents is no longer confined to the developed countries; it has spread to the developing countries as well. The culture of fast food consumption has replaced the traditional meal among university students and is a great public health concern. Excessive consumption of fast food is responsible for obesity epidemics and the cause of a dramatic increase of obesity-related diseases (e.g. diabetes, heart diseases etc). A cross-sectional study was carried out from March to April, 2013 among students attending in four established private universities of Bangladesh situated in Dhanmondi, Dhaka: Daffodil International University, United International University, World University of Bangladesh, and State University of Bangladesh. The aim of the present study was to examine the preference, prevalence and pattern of fast food consumption among the students. The prevalence of fast food consumption among those students was 98.5%, and 43.3% of their pocket money was spent on its purchase. The important factors for the preference of fast food include good taste, easy accessibility, increased convenience, and pocket friendly in nature. Approximately 22% of the respondents mentioned that they consumed fast food 4 days per week and more than one-fifth had the meal every day. Fifty four percent of the respondents skipped their breakfast due to a variety of reasons including class pressure and had fast food after fin-ishing their classes, either from varsity canteens or other fast-food outlets. Though 98% of the students were well informed about the negative effects associated with excessive fast food consumption, they were still profoundly ad-dicted to it. Specific health education programs, dietary guidelines and effective public awareness campaigns could be initiated to address the unhealthy lifestyle of university students and improve their health. South East Asia Journal of Public Health 2013; 3(1): 61-64 DOI: http://dx.doi.org/10.3329/seajph.v3i1.17713